BONINITES THROUGH TIME AND SPACE: PETROGENESIS AND GEODYNAMIC SETTINGS - A. A. Shchipansky (Геодинамика и тектонофизика, 2016)
The article provides an overview of boninitic magmatism occurrences in space and time and shows that the boninite rock series were generated through the entire geological history of the Earth. In modern environments, the genesis of boninites is related to intra‐oceanic subduction initiation. Boninites are typical members of suprasubduc‐ tion zone ophiolite sequences in the Phanerozoic fold belts and also present in the early Precambrian greenstone belts. A comparative study on compositions of the early Precambrian and Phanerozoic boninites indicate their evolu‐ tion through time due to gradual transition from the early thick‐plate tectonics to the modern thin‐plate tectonics. A link between subduction initiation and mantle‐plume impingement at the oceanic lithosphere is discussed.